Mengungkap Implementasi PSAK No. 34 pada Perusahaan Konstruksi Y - Devi Novianti; Rusliyawati; Desyana, Gita (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
This reseach purpose is to (isi abstract menyesuaikan abstrak) This research aims to evaluate the implementation of Revenue Recognition based on PSAK 34 in Construction Company Y, focusing on road preservation projects. Using a descriptive qualitative approach, the study involves the analysis of the utilization of the completed contract method compared to the percentage of completion method by the company. Data were gathered through interviews and documentation. In road preservation projects, the application of the completed contract method is seen as consistent with PSAK 34. However, the findings reflect that the company has not fully complied with PSAK 34 since the same method has been utilized for long-term projects, despite the standard mandating the use of the percentage of completion method for such projects. Research recommendations emphasize the need to transition from the completed contract method to the percentage of completion method for long-term projects to ensure complete consistency to PSAK 34 standards and alignment with the diverse project characteristics.